(untitled) (Revista Cercurilor studenţeşti ale Departamentului de Limba şi Literatura Franceză, 2025)
Legal translation has a privileged position in the language industry these days, yet machine translation, however significant the advances in technology (neural translation, deep learning, AI, large language models) and despite the massive digitization of normative texts and case law, seems to perform less well precisely in this field. The aim of our research is to illustrate this dynamic through a case study and to investigate the reasons for it.